A DESCRIPTIVE STUDY OF STUDENTS PERCEPTION ON THE ONLINE LEARNING IMPLEMENTATION DURING COVID-19 OF ENGLISH EDUCATIONAL DEPARTMENT STUDENTS AT PGRI UNIVERSITY OF BANYUWANGI - Devi Fatimatus Zuhro; Tri Mulyati; Sutami Dwi Lestari (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2022)
Online learning is the best solution for the teaching and learning process during Covid-19 pandemic.This study aims to determine students’ perceptions on the online learning implementation. The research method used in this research is survey method. The respondents were the all of students on English Educational Department at PGRI University of Banyuwangi. The technique sampling used the purposive sampling. The data collection method was carried out by filling out the questionnaire through Google Form and interviews to find out the students has a good or bad perception on the online learning implementation. The result of this research regarding the student’s perception on the online learning implementation during Covid-19 of English Educational Department students at PGRI Banyuwangi University is in the good category with the overall percentage is 65%. For the result of the interviews, the implementation on the online learning during Covid-19 pandemic can help them to carrying out the learning process easier. However, there are still some obstacles of the implementation on the online learning such as lack of understanding and an unsupported internet network. As for suggestion from the researcher, the students should be actively looking for the materials from the other sources, not only receive from the lecture. It aims to make the learning process more effective.